A Laboratory Study of the Elastic and Anelastic Properties of the Eagle Ford Shale. - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (2015)
We present the preliminary results of the low-frequency and ultrasonic experiments conducted on a shale sample recovered from the Eagle Ford shale (South Texas). The shale sample was cut in the direction perpendicular to the formation bedding and tested in dry and wet states to estimate the effect of water presence on elastic properties and attenuation. The elastic parameters obtained for the shale at seismic (0.1 – 100 Hz) and ultrasonic (~0.5 MHz) frequencies are very close in both dry and wet conditions. Extensional attenuation and dispersion measured in the frequency range between 0.1 Hz and 100 Hz were inessential. The interpretation of the obtained results within the theoretical models of partial saturation is discussed.